COVID-19 and fertility services in the United Kingdom: a biphasic qualitative study - B Karavadra; A Stockl; A H Balen; E P Morris (Bioscientifica, 2021)
Recently, fertility services have started resuming since COVID-19 was declared a pandemic, but there remains significant uncertainty in the way this care will be delivered in the United Kingdom. The objective of our study was to explore the impact of COVID-19 on individuals using fertility services in the United Kingdom. The study was conducted in two phases between May 2020 and July 2020: an online questionnaire involving 1212 participants and subsequent individual semi-structured telephone interviews with 15 participants. Through thematic analysis, we learned from the questionnaire findings that 74% of individuals identified as White British, 21% as Black and Minority Ethnic (BAME) and 2.6% as male. Ninety-six per cent of individuals from the questionnaire explained that COVID-19 had a 'negative impact' on their fertility treatment, namely 'delay in care'. Eighty-two per cent of participants discussed concerns about the 'uncertainty' they felt about fertility services; these included the 'unknown impact of COVID-19 on pregnancy outcomes', the 'unknown impact on general gynaecology services' and the 'unknown impact of COVID-19 on fertility success'. Through semi-structured telephone interviews with 15 participants, we learned about the 'cultural pressures' individuals from BAME backgrounds faced in relation to care. Participants were mindful about the 'pressures on the service' when reopening, and therefore 'advancing maternal age', 'socio-economic background' and 'previous unsuccessful fertility treatment' were the main factors individuals considered important when 'prioritising' fertility care. Our findings can be used by fertility service providers to appreciate the patient perspective when considering the reopening of fertility services nationally and internationally.